(untitled) (Journal of Applied Learning and Teaching, 2023)
The Covid-19 pandemic created the need for (often rapid) transitions to online delivery in many higher education settings. As the world transitioned to living with the pandemic, the need to adequately support students with health concerns about returning to campus, either for themselves or those with whom they were living, plus a range of other access issues, created the need to shift to a hybrid delivery mode in many places. This study examines the student experiences of hybrid delivery in a TNE branch campus in the United Arab Emirates and their suggestions for how hybrid delivery could be improved for future delivery. The study employed open-ended survey questions to ask about the most effective, least effective and improvement areas from students who were enrolled in hybrid courses. The responses were analysed, and after examining the data provided in the survey, some measure of success in implementing a hybrid delivery model has been identified. However, a number of areas for concern were also raised in the responses. Additionally, students also identified solutions to some of the problems to improve the quality. Issues with technology, engagement, support and the benefit of remaining online in hybrid mode were some of the least and most effective issues raised by the students.